Primary Stenting for Acute Myocardial Infarction - Peter, J.; Yhip, A.; Smalling, Richard W. (Thrombosis and Haemostasis, 1999)
Primary stenting for acute MI has been shown to be an improvement over PTCA alone. As with primary PTCA however there is an obligate delay in restoration of TIMI flow due to the time necessary for mobilization of the cath lab team. It is possible that a hybrid approach using partial thrombolysis plus early IIB/IIIA inhibitor administration followed by urgent angiography and stenting of the culprit lesion will be the ideal approach.
Keywords: Stenting; PTCA; revascularisation